INCUBADORA DE ECONOMIA SOLIDÁRIA E DESENVOLVIMENTO SUSTENTÁVEL: SEUS PROPÓSITOS, SUAS PRÁTICAS. - Barcelos, Eronita S.; Rasia, Pedro C.; Basso, Lauri; Lechat, Noelle M. P. (Salão do Conhecimento, 2013)
Resumo